2018
DOI: 10.1007/s00394-018-1661-x
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin acts anti-inflammatory on murine IL-10−/− colitis and human intestinal fibroblasts

Abstract: Nobiletin decreases inflammatory symptoms and markers in murine colitis as well as fibrotic collagen deposition and expression. Thus, nobiletin could be a potential new agent in therapy of chronic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Later, the same research group further investigated the impact of nobiletin on in vivo IL-10 −/− mice model. Evidence showed that nobiletin treated mice exhibit significant reduction in colitis clinical symptoms, mast cell numbers, mast cell degranulation and cellular infiltration (Hagenlocher et al, 2018), which may provide very useful reference for clinical application of nobiletin. Wang et al…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 96%
“…Later, the same research group further investigated the impact of nobiletin on in vivo IL-10 −/− mice model. Evidence showed that nobiletin treated mice exhibit significant reduction in colitis clinical symptoms, mast cell numbers, mast cell degranulation and cellular infiltration (Hagenlocher et al, 2018), which may provide very useful reference for clinical application of nobiletin. Wang et al…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 96%
“…People enjoy unique varieties of citrus because of their refreshing flavor and nutritional value. Citrus natural products, especially the flavonoids, have become a hot research topic because of their diverse biological activities [1,2,3]. Polymethoxyflavones (PMFs) are an essential type of flavonoids in citrus, characterized by more than or equal to four methoxy substitutions in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the murine IL-10 knockout model of colitis, treatment with the citrus flavonoid nobiletin resulted in a reduction of clinical colitis and a reduction of mast cell number and degranulation, which correlated positively with disease activity indexes [ 179 ].…”
Section: Nutraceuticals Affecting Mast Cell Activitymentioning
confidence: 99%